MECP2 mutation in non-fatal, non-progressive encephalopathy in a male. Issue 3 (1st March 2001) - Imessaoudene, Belaïd; Bonnefont, Jean-Paul; Royer, Ghislaine; Cormier-Daire, Valérie; Lyonnet, Stanislas; Lyon, Gilles; Munnich, Arnold; Amiel, Jeanne
Abstract : To study the clinical overlap between Rett (RTT) and Angelman syndromes (AS), we screened the MECP2 gene in a cohort of 78 patients diagnosed as possible AS but who showed a normal methylation pattern at the UBE3A locus. MECP2 missense (R106W, G428S), nonsense (R255X, R270X), and frameshift mutations (803 delG) were identified in 6/78 patients including 4/6 female cases consistent with RTT, one female case with progressive encephalopathy of neonatal onset, and one isolated male case with non-fatal, non-progressive encephalopathy of neonatal onset. This study shows that MECP2 mutations can account for a broad spectrum of clinical presentations and raises the difficult issue of the screening of the MECP2 gene in severe encephalopathy in both males and females.